Market Design for Altruistic Supply: Evidence from the Lab - Robert Slonim; Carmen Wang (Institute for the Study of Labor (IZA), 2016)
Volunteer supply is widespread, yet without a price inefficiencies occur due to suppliers' inability to coordinate with each other and with demand. For these contexts, we propose a market clearinghouse mechanism that improves efficiency if supply is altruistically provided. The mechanism, a registry, combines aggregate demand information with supplier's willingness to help, and invites volunteers to help only when excess demand occurs. We experimentally study three registries that include stochastic high-stakes demand and heterogeneous supplier costs. We find that all three registries improve efficiency dramatically; they eliminate unneeded costly help when demand is unexpectedly low and significantly increase supply (reduce shortages) otherwise. Further, two registries that invite exactly one registry member to help for each person needing help, rather than the third registry that continues asking members to help until someone helps, result in fewer people joining the registry, but those who join are more likely to help.
Keywords: D47; D64; C93; 330; market design; laboratory experiments; volunteering; public goods provision